1999
DOI: 10.1177/088840649902200402
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Reciprocal Peer Coaching on Preservice General Educators' Instruction of Students with Special Learning Needs

Abstract: Most students with special learning needs spend a good proportian of their time in school in general education classrooms. There is ample reason to suspect, however, that many general educators are not prepared adequately to meet their extensive instructional needs. This evidence becomes even more compelling when one considers the initial preparation of beginning teachers. In this study, we attempted to improve the instructional performance of three dyads ofpreservice teachers who were tutoring students with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…A peer-feedback model, unlike a one-time classroom observation, is all-encompassing—providing feedback about everything from learning objectives to assessment strategies—rather than just evaluating the in-class performance. In this model, instructors regularly observe one another, providing support, feedback, and assistance in order to improve one another's instructional practices ( Mallette et al. , 1999 ; Weimer, 2002 ; Huston and Weaver, 2008 ).…”
Section: Overcoming Existing Barriers: Strategies For Recipients Of Fmentioning
confidence: 99%
“…A peer-feedback model, unlike a one-time classroom observation, is all-encompassing—providing feedback about everything from learning objectives to assessment strategies—rather than just evaluating the in-class performance. In this model, instructors regularly observe one another, providing support, feedback, and assistance in order to improve one another's instructional practices ( Mallette et al. , 1999 ; Weimer, 2002 ; Huston and Weaver, 2008 ).…”
Section: Overcoming Existing Barriers: Strategies For Recipients Of Fmentioning
confidence: 99%
“…Single subject, quasi-experimental, and group design studies within P-12 general and special educators have demonstrated peer and BIE coaching’s efficacy in improving candidates’ practice (Johnson, Finlon, Kobak, & Izard, 2017; McKinney & Vasquez, 2014; Ploessl & Rock, 2014; Scheeler, McKinnon, & Stout, 2011), reflection (Lu, 2010), and, in some cases, student achievement (Mallette, Maheady, & Harper, 1999). Rock and her colleagues (2014) add a longitudinal study providing evidence that BIE coaching led to improvements in teachers’ practice that were still visible 2 years following this coaching.…”
Section: Analysis Of Practice-based Opportunitiesmentioning
confidence: 99%
“…For instance, training teachers on team learning prior to PTL was perceived to benefit collaboration activities (Main, 2012;Shriki & Movshovitz-Hadar, 2011). Furthermore, training student teachers in coaching activities was demonstrated to enhance the success of implementation of literacy teaching skills (Mallette, Maheady, & Harper, 1999).…”
Section: Contexts Influencing Ptl Activitiesmentioning
confidence: 99%